An Unusual Case of Tooth in the Floor of the Orbit: The Libyan Experience. (30th September 2012) - Shetty, Y. Naresh; Majid, Irfan Adil; Patel, Raju Umaji; Shammam, Musbah
Abstract : Maxillary dentigerous cysts although uncommon need to be considered in the differential diagnosis in children with painless facial swelling. We present a case of dentigerous cyst associated with maxillary deciduous canine and maxillary premolars manifesting as a unilateral swelling in canine region of the face. A ten-year-old boy came to oral and maxillofacial surgery unit with a painless left facial swelling. The local dentist had prescribed antibiotics for treatment for the facial swelling, but the swelling did not subside, and the parents brought the child to our unit in Zliten Dental College. After clinical examination and imaging, the diagnosis of dentigerous cyst was made. Caldwell-Luc approach was done, the cyst was enucleated, and primary closure was done. The patient was followed up for a period of two years and there was no evidence of any recurrence.